2017
DOI: 10.1063/1.4996956
|View full text |Cite
|
Sign up to set email alerts
|

Sub-500 fs electronically nonadiabatic chemical dynamics of energetic molecules from the S1 excited state: Ab initio multiple spawning study

Abstract: Energetic materials store a large amount of chemical energy. Different ignition processes, including laser ignition and shock or compression wave, initiate the energy release process by first promoting energetic molecules to the electronically excited states. This is why a full understanding of initial steps of the chemical dynamics of energetic molecules from the excited electronic states is highly desirable. In general, conical intersection (CI), which is the crossing point of multidimensional electronic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The release of energy by these compounds follow relatively complicated reaction mechanisms. , Uncovering the quantum chemical dynamics of these compounds, from the microscopic viewpoint, can help chemists design new and more efficient energetic compounds.…”
Section: Unit 1: a Chemical Introduction To Quantum Computingmentioning
confidence: 99%
“…The release of energy by these compounds follow relatively complicated reaction mechanisms. , Uncovering the quantum chemical dynamics of these compounds, from the microscopic viewpoint, can help chemists design new and more efficient energetic compounds.…”
Section: Unit 1: a Chemical Introduction To Quantum Computingmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, new interpretations of bifurcating transition states as well as molecules with large excited-state nuclear displacements have emerged to challenge the notion that a single reaction coordinate trajectory dominated by thermodynamics is capable of adequately describing complex excited-state reactivity. 4,6,7 The origin of these changes in interpretation is found in reactions where a transition state is located near a stationary point (location on the potential energy surface where energy gradients with respect to the nuclear position are small or zero) or a conical intersection thus enabling non-equilibrium molecular dynamics to dictate reaction outcomes over thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nitro groups significantly changes the photochemical and photophysical behavior of molecules and affect the stability and sensitivity of energetic molecules [ 4 , 5 , 6 ]. Recent literature shows [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] excited energetic molecules deactivated from the S 1 excited state to the S 0 ground state through a conical intersection (CI). Experimental and theoretical studies by Bernstein and coworkers [ 6 ] found that the conical intersection plays an important role in the non-adiabatic decay of the energetic molecule dimethylnitramine (DMNA).…”
Section: Introductionmentioning
confidence: 99%